2021
DOI: 10.1088/1742-6596/1783/1/012121
|View full text |Cite
|
Sign up to set email alerts
|

Kahoot Application for Elementary School Students: Implementations of Learning Process from Distance during Pandemic period of COVID 19

Abstract: Kahoot Applications has been one of the media of the learning process to be developed further. It can become media of the learning process as well as a tool for measuring/index of the target. These analyses observe the result of the learning process based on Kahoot Application towards the fifth grade of elementary students in the context of single and complexes theory. This kind of Media of learning process is more likely effective used in the argent situation of the Pandemic COVID 19 period that is inevitable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
11

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 2 publications
0
12
0
11
Order By: Relevance
“…Selanjutnya dalam hal pelajaran IPA oleh (Djannah et al, 2021) mengenai materi yang masih kurang dipahami peserta didik, hasil respon yang didapatkan dari pendidik dan peserta didik dengan pilihan yang lebih banyak memiliki kesamaan jawaban yakni pada materi cahaya. Dan dilanjutkan pada bagian detail dari materi tersebut, alasan yang diberikanpun juga sama yakni dalam hal penjelasan cermin.…”
Section: Responden Peserta Didikunclassified
“…Selanjutnya dalam hal pelajaran IPA oleh (Djannah et al, 2021) mengenai materi yang masih kurang dipahami peserta didik, hasil respon yang didapatkan dari pendidik dan peserta didik dengan pilihan yang lebih banyak memiliki kesamaan jawaban yakni pada materi cahaya. Dan dilanjutkan pada bagian detail dari materi tersebut, alasan yang diberikanpun juga sama yakni dalam hal penjelasan cermin.…”
Section: Responden Peserta Didikunclassified
“…Material experts focus on content because the material in VR media is an essential part of student knowledge to get special attention. The relevant research showed the content qualification aspect had the highest results so that it had a very significant effect on the suitability of the material in the resulting VR technology (Djannah et al, 2021;Herbert et al, 2021). Thus, all aspects of this material expert are perfect and following the learning needs of students.…”
Section: Discussionmentioning
confidence: 99%
“…Munculnya pandemi Covid-19 secara tiba-tiba, tidak dapat dipungkiri bahwa pendidikan di Indonesia perlu fleksibel untuk membantu situasi pendidikan di sekolah dasar dalam keadaan darurat ini (Djannah et al, 2021). Pandemi Covid-19 menyebabkan perubahan besar pada bidang pendidikan dimana sekolah tidak dilakukan secara tatap muka namun dilakukan dengan pembelajaran jarak jauh atau daring.…”
Section: Pendahuluanunclassified